Profile of fatal road traffic accidents in Pune region, Maharashtra: A cross sectional autopsy study - Punpale, S B; Taware, A A; Vaidya, H V; Tatiya, H S (Journal of Indian Academy of Forensic Medicine, 2019)
Road traffic accidents are unpremeditated events resulting in recognizable damage. In India, road traffic injuries will be the third  leading cause of death by 2020. The present study reflects the data received from victims of road traffic accidents brought to mortuary  of the Department of Forensic Medicine and Toxicology, BJGMC, Pune from May 2018 to September 2018. The overall prevalence of  road traffic accident cases was 32.20 %, where the majority were from the age group 21-30 years. Male victims outnumbered female  victims and thoracic injuries were highest (31.95 %) amongst all other causes of death. The most common internal organs to get injured  were lungs. Data also reflects the highest occurrence of a road traffic accident between 06 pm to 12 mid-noon.
Keywords: Road traffic accident; Mortuary; Thoracic injuries; Internal organs